Correction to: The private healthcare market and the sustainability of an innovative community nurses programme based on social entrepreneurship - CoNSENSo project - Roberto Ippoliti; Greta Falavigna; Floriana Montani; Silvia Rizzi (BMC, 2018)
Following publication of the original article [1], the author reported that their first names and last names were swapped. The original article has been corrected.